2020
DOI: 10.5539/jmsr.v9n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Thermosets Obtained by Copolymerization of Humins with Triglycidyl Ether of Phloroglucinol

Abstract: The environmental pollution is growing continuously -causing a worldwide problem. Production and use of petroleum-based materials but also huge quantities of industrial wastes are important factors that affect the wellbeing of the environment. New scientific researches place great emphasis on waste valorization, and also on developing new environmentally friendly bio-based materials. In this work we focus on the valorization of humins, a biorefinery side product, by its copolymerization with a bio-based triepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Especially this aspect has challenged our previous work and studies for developing proper strategies for the humins-based materials design. Based on intense and thorough studies, [28][29][30][31] we found that copolymerization of humins with different epoxides generate materials with modulated mechanical properties from elastic to rigid, with a long lifespan, their physico-chemical and mechanical characteristics remaining optimal over time. The use of humins in large quantities (55 wt.%), the use of renewable, cheap, and industrially available co-reactants, the development of materials through cost competitive processes, but especially the tailoring of rigid furan materials with competitive thermo-mechanical properties for various industrial sector, made the resin used for this study a good candidate for testing the influence of humins composition on the final properties of the resulting materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially this aspect has challenged our previous work and studies for developing proper strategies for the humins-based materials design. Based on intense and thorough studies, [28][29][30][31] we found that copolymerization of humins with different epoxides generate materials with modulated mechanical properties from elastic to rigid, with a long lifespan, their physico-chemical and mechanical characteristics remaining optimal over time. The use of humins in large quantities (55 wt.%), the use of renewable, cheap, and industrially available co-reactants, the development of materials through cost competitive processes, but especially the tailoring of rigid furan materials with competitive thermo-mechanical properties for various industrial sector, made the resin used for this study a good candidate for testing the influence of humins composition on the final properties of the resulting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Humins were also used in the preparation of porous carbon materials with variable industrial applications such as substrates for plant growth, absorbents for wastewater treatment, insulation materials, support for solid catalysts, etc [17–23] . Humins revealed moreover a real potential in the development of polymeric resins and composites, being still in the incipient phase of research [24–28] . Humins itself have a peculiar reactivity generating porous and brittle materials, due to its complex and polyaromatic structure and presence of the various functional groups (−OH, aldehyde and ketone groups).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant compound used in this study, a biorefinery derived side-product, are the humins, which are generated in the production of furandicarboxylic acid) [37][38][39][40]. Humins are composed mainly of aromatic rings, containing different functionalities varying in function of biorefinery processing: aldehydes, hydroxyls, carboxylic and ketones.…”
Section: Introductionmentioning
confidence: 99%
“…These reactive groups make the humins promising building block and an important compound for the development of thermosetting resins . [30,37,38,40,41,42 ].…”
Section: Introductionmentioning
confidence: 99%